Modelling boreholes in complex heterogeneous aquifers. (August 2019) - Upton, K.A.; Butler, A.P.; Jackson, C.R.; Mansour, M.
Abstract: Reliable estimates of the sustainable yield of supply boreholes are critical to ensure that groundwater resources are managed sustainably. Sustainable yields are dependent on the pumped groundwater level in a borehole, how this relates to vertical aquifer heterogeneity, and features of the borehole itself. This paper presents a 3D radial flow model (SPIDERR), based on the Darcy-Forchheimer equation, for simulating the groundwater level response in supply boreholes in unconfined, heterogeneous aquifers. The model provides a tool for investigating the causes of non-linear behaviour in abstraction boreholes, which can have a significant impact on sustainable yields. This is demonstrated by simulating a variable-rate pumping test in a Chalk abstraction borehole. The application suggests the non-linear response to pumping is due to a combination of factors: a reduction in well storage with depth due to changes in the borehole diameter, a reduction in hydraulic conductivity with depth, and non-Darcian flow. Highlights: New model – SPIDERR – presented for simulating boreholes in complex aquifers. SPIDERR represents key features of a borehole and unconfined heterogeneous aquifer. SPIDERR is based on the Darcy-Forchheimer equation to simulate non-linear flow. SPIDERR shown to reproduce non-linear groundwater level response in a Chalk borehole.